Gamification Experience in Secondary Education on Learning of Digital Systems - Jesús Carlos DÍEZ RIOJA; David BAÑERES BESORA; Montse SERRA VIZERN (Ediciones Universidad de Salamanca, 2017)
Games have always been used in order to motivate learning at early ages. Nevertheless, during teen years, playing games have often been stigmatized as a waste of time. Thus, the phenomenon of gamification has become recently a methodological trend with a relevant presence in the classroom. In this paper, an analysis of previous work in gamification is performed in primary and secondary education. Next, the experience carried out at a secondary school in Barcelona is described where a program has been implemented ad hoc to teach, in a playful way, contents of digital systems in the context of the Industrial Technology course in secondary school. The results of the experience and the students' opinion that have been positive are summarized in this paper.